Strategic impact: Technical fouls and momentum shifts in basketball games - unveiling insights across quarters of two decades of NBA data - Lev, A.; Maymon, Y. K.; Zion, T. B.; Tenenbaum, G. (International Journal of Sports Science & Coaching, 2025)
Spanning two decades (2000-2021), this study examines the frequency and timing of technical fouls (TFs) committed by NBA coaches, and their relationship with momentum shifts throughout the quarters of a basketball game. A big data of 4,196TFs calls of NBA coaches was used to elucidate TFs association with momentum shifts, considering location, scoring position, and quarter. Logistic regression revealed higher momentum shift and win probabilities when TFs were called while the team was ahead (70% vs. 22%) and in home games (44% vs. 22%). At home, TFs calls during trailing position decreased win chances from 41% (Q1) to 10% (Q4), but when committed in a winning position, the win chances increased from 62% (Q1) to 84% (Q4). Lower TFs effects were observed in away games. Specifically, TFs during trailing position reduced win chances from 33% (Q1) to 6% (Q4), while in advantage TFs increased win chances from 44% (Q1) to 79% (Q4). The differences evident in momentum shifts due to environmental and specific situational factors are attributed to changes in the interaction among the team's motivational climate, collective efficacy, and the spectators` drive.